Pengaruh Earnings Per Share (EPS) Terhadap Harga Saham Pada PT United Tractors Tbk - Gleashella Aurellya; Giovina Gloria; Felicia Tirta Kelana; Elizabeth Tiur Manurung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the influence of Earnings per Share (EPS) on Stock Price in PT United Tractors Tbk. This research uses the quarterly financial reports on PT. United Tractors Tbk which is based in Indonesia as its source of data. This research employed a quantitative descriptive method by analyzing the results of a simple linear regression. Based on the regression data, a positively significant impact of EPS on Stock Price is found, where changes in EPS are followed by the changes in Stock Price.